Communication with patients with limited prognosis: an integrative mixed-methods evaluation study - Siegle, Anja; Unsöld, Laura; Deis, Nicole; Krug, Katja; Bossert, Jasmin; Krisam, Johannes; Jung, Corinna; Jünger, Jana; Wensing, Michel; Thomas, Michael; Villalobos Bollen, Matthias Americo (Supportive care in cancer, 2023)
Oncological societies advocate the continuity of care, specialized communication, and early integration of palliative care. To comply with these recommendations, an interprofessional, longitudinally-structured communication concept, the Milestone Communication Approach (MCA), was previously developed, implemented, and evaluated. Our research question is: what are possible explanations from the patient perspective for prognosis and advance care planning being rarely a topic and for finding no differences between MCA and control groups concerning distress, quality of life, and mood?
Online veröffentlicht am 22. Dezember 2022
Gesehen am 07.02.2023